Exploring Perceptions of Workplace Bullying in Nursing - Eve Butler; Andrea Prentiss; Flora Benamor (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2018)
Introduction: Bullying is experienced by all levels of nurses and in all practice settings. The impact of bullying in the workplace environment can have significant negative effects on morale and may lead to increased turnover. As a result of a referral to the Nursing Quality Council for bullying, the Nursing Quality and Caring Council set forth to explore bullying in the workplace. The purpose of this study was to identify registered nurse/clinical partner perceptions of the frequency and prevalence of bullying in the workplace and to assess registered nurses' (RNs) experiences of bullying by physicians, coworkers, patients and direct supervisors. Methods: Using a descriptive cross sectional survey design, RNs were offered two surveys; the Nursing Incivility Scale (NIS) and the Negative Acts Questionnaire (NAQ). Clinical Partners were offered the NAQ only. Results: Participants included 386 RNs and 98 clinical partners (CPs). Nurses reported patient and families take their frustrations out on the nurse as the highest score on the Nursing Incivility Scale. Both RNs and CPs reported being exposed to an unmanageable workload as the number one source of bullying in the Negative Acts Questionnaire. Overall, the results revealed 31% of participants reported experiencing bullying on some level within the last 6 months. Discussion: The results of this study support the literature suggesting bullying continues to be present in the workplace. These findings support the need for an organizational action plan designed to eliminate bullying in the workplace.